Development and evaluation of a tractor-operated automatic gun sprayer for cotton crop - T, Nagesh Kumar; Anantachar, M; Veerangouda, M; Prakash, KV; Nadagouda, S; Koppalkar, BG; Advi Rao, Sushilendra; Murali, M; Raghavendra, V (African Entomology, 2022)
A tractor-operated automatic gun sprayer was developed for the cotton crop. The unit consists of frame structure, spray tank, horizontal triplex pump, control valves, spray gun nozzle, pressure gauge, strainer, hydraulic agitator and actuating mechanism. The power to drive the HTP pump was taken from the tractor power take off (PTO) through a belt and pulley. The actuating mechanism consists of motor and worm gear reduction. Two motors with 0.5 kW each (12 V dc) were used to provide oscillation motion to spray guns and motors get power from the tractor battery. The rotation angle of the spray gun is 30° horizontally. Provision was also made to fold the spray boom while in transport. The spray pattern could be adjusted based on the application of chemicals. This study was conducted to determine the suitable nozzle orientation (0, 15 and 30° downwards) to field crops. The orientation of the spray nozzle was maintained by using the metal protractor. The laboratory experiments were carried out by using the actual cotton plant. The best nozzle orientation for maximum droplet density and droplet size as 15° downward. Leaf hopper [Amrasca biguttula (Ishida)] and aphids [Aphis gossypii (Glover)] control in the cotton crop after 7th day of spraying dinotefuran insecticide from the automatic gun sprayer and conventional tractor-operated gun sprayer was 87, 86 and 58 %, and 50 %, respectively. The total cost required to fabricate the sprayer was US 1008. The cost of operation of the tractor operated automatic gun sprayer was found to be US 4.7/ ha.